Harvard Medical School, ca. 1890 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east of Harvard Medical School, located at the southeast corner of Boylston and Exeter Streets. The Boston Public Library is visible to the east or to the left of the medical school building. The Boston Athletic Association is located to the south or behind the medical school. A small For Sale sign is visible in front of the northwest corner of the Harvard Medical School building. 7 15/16 x 6, 9 3/8 x 7 3/8 overall Photographs